Inflammatory Myofibroblastic Tumor of the Breast - Christos Markopoulos; Petros Charalampoudis; Evangelia Karagiannis; Zoh Antonopoulou; Dimitrios Mantas (Case Reports in Surgery)
Inflammatory myofibroblastic tumors (IMTs) of the breast represent extremely rare lesions. Due to the scarcity of reports, their natural history, recurrence, and metastatic potential remain poorly defined. We report on a case of a primary breast IMT in a postmenopausal female patient treated successfully with breast conserving surgery and review the literature pertaining to this rare entity.